Mulheres entre enfeites & caminhos: cartografia de memórias em saberes e estéticas do cotidiano no Marajó das florestas (S.S. da Boa Vista – Pa) - JARDIM, Ninon Rose Tavares (Universidade Federal do Pará, 2017)
This research presents a mapping of know-how with jupati fibers, woven by women from rivers Pirarara, Seringueiro, Urucuzal and the Village of Nazaré, in São Sebastião da Boa Vista city, at the Marajó Forest, state of Pará, Brazil. The problem that guided this research was to analyze how these forest marajoara women build know-how in the artistic creativity of weaving fibers and what are the meanings of this art in their lives and how their works dialogue with tradition and contemporary. Also, how this art has been (re) meaning over the years. Following theoretical orientations of Cultural Studies and Postcolonial Thought in connection with the field of Art and through the methodology of oral history, ethnography sought the physical landscape, people and culture of a rural community in the Amazonia. And so capture the aesthetic developed in daily life, the senses of know-how gestated in making ornaments and paths between forms and colors. From this, I analyze the creative and production process during the making fiber in relation to the times of marajoara way of living. I present a discussion of how this art is absorbed by the market; bring to the art scene in fiber jupati conceptual issues in dialogue with the art field, linking tradition and modernity, classical and popular art and aesthetics of daily life, interwoven looks to women about their work and the symbolic, aesthetic and formal meanings. I try to get approximations with memories indigenous heritages and histories as correlating Ornaments and Paths. Its chromatic relations, roles that art plays in the lives of these women and the iconic, indexical and symbolic meanings of artistic compositions. Absorbed by this universe, I find that the know-how fiber is articulated to cosmologies and ecosystems aesthetic; fiber art is knowledge and livelihood; Works expressing feelings of pleasure, like weaving, urging transgressions of cosmological local codes; strengthen family ties; moments of intimacy, complicity, learning, disputes, achievements between mothers, daughters and sisters; (re) affirm identities, artistic authorities, establishing codes of respect and hierarchies in the recognition about the quality of the weave.